Leksikon Mantra Pengobatan pada Ritual Balian Pengobatan dalam Masyarakat Desa Pendreh Kabupaten Barito Utara - Santang Santang (Jurusan Dharma Acarya STAHN-TP Palangka Raya, 2022)
Treatment techniques in the Dayak community of Pendreh Village, North Barito Regency still maintain traditional medicine techniques, namely the Balian ritual. The purpose of carrying out the Balian treatment ritual is to ask God for health through the intermediary of Sangiang whose power was borrowed by Basir in the ritual. This study aims to describe the Lexicon of Healing Mantras on Balian Rituals in the Pendreh village community, North Barito Regency. The results of this study show that there is a relationship between language and community culture. The language spoken in the form of mantras influences the treatment system that has an order in society. it also strengthens the ties of friendship between community members. The results of this study also explained the ritual implementers with their respective duties. In addition, there is also a list of ritual lexicons of Balian medicine rituals which are presented in tabular form.